Mesenchymal stem cell secretome-loaded fibrin glue improves the healing of intestinal anastomosis - Yu, Wenwen; Zhou, Haicun; Feng, Xueliang; Liang, Xiaoqin; Wei, Dengwen; Xia, Tianhong; Yang, Bin; Yan, Long; Zhao, Xiaochen; Liu, Hongbin (Frontiers in Bioengineering and Biotechnology, 2023)
Anastomotic leakage is a serious complication following gastrointestinal surgery and one of the leading causes of patient mortality. Despite the significant clinical and economic burden, there are currently no reliable treatment options to improve the healing of intestinal anastomosis and subsequently prevent anastomotic leakage. Recently, the development of regenerative medicine has shown promise for improving anastomotic healing. Recent studies have illustrated that stem cell-derived secretome can enhance tissue regeneration without the safety and ethical limitations of stem cell transplantation. Herein, we developed a fibrin glue topical delivery system loaded with mesenchymal stem cells (MSCs)-derived secretome for controlled delivery of bioactive factors, and evaluated its application potential in improving the healing of intestinal anastomosis. Under in vitro conditions, the MSCs secretome significantly promoted cell proliferation viability in a dose-dependent manner and resulted in the controlled release of growth factors via fibrin glue delivery. We established a rat surgical anastomotic model and experimentally found that MSCs secretome-loaded fibrin glue enhanced anastomotic bursting pressure, increased granulation tissue formation and collagen deposition, and significantly promoted anastomotic healing. Mechanistically, fibrin glue accelerated cell proliferation, angiogenesis, and macrophage M2 polarization at the surgical anastomotic site by releasing bioactive factors in the secretome, and it also alleviated the inflammatory response and cell apoptosis at the anastomotic site. Our results demonstrated for the first time that MSCs-derived secretome could promote the healing of intestinal anastomosis. Considering the accessibility and safety of the cell-free secretome, we believed that secretome-loaded fibrin glue would be a cell-free therapy to accelerate the healing of intestinal anastomosis with great potential for clinical translation.